Teacher training for hospital classes: Brazilian reality - Aline FERREIRA RODRIGUES PACCO; Adriana GARCIA GONÇALVES (Ediciones Universidad de Salamanca, 2018)
Considering the importance of the hospital educational service and the teacher training of the teachers who work in this service, the present study had the objective of describing the teacher preparation for hospital classes in the national scope. He carried out a field study using a survey technique. Thirty-three teachers from different Brazilian states participated in the present study, answer ing a online questionnaire. The data showed that most of the teachers in their initial formation have a degree in Pedagogy. In the context of continuing education, it is noticed that most of the professors have chosen training individually and with their own incentive, seeking specialization courses as a source of new knowledge. It is concluded that there are still many gaps in the training of the hospital-class teacher, and there are no specific public policy that guide the adequate training of these teachers who are inserted in such a distinguished environment as the hospital class.